2020
DOI: 10.3390/cancers12123529
|View full text |Cite
|
Sign up to set email alerts
|

Current Progresses and Challenges of Immunotherapy in Triple-Negative Breast Cancer

Abstract: With improved understanding of the immunogenicity of triple-negative breast cancer (TNBC), immunotherapy has emerged as a promising candidate to treat this lethal disease owing to the lack of specific targets and effective treatments. While immune checkpoint inhibition (ICI) has been effectively used in immunotherapy for several types of solid tumor, monotherapies targeting programmed death 1 (PD-1), its ligand PD-L1, or cytotoxic T lymphocyte-associated protein 4 (CTLA-4) have shown little efficacy for TNBC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 276 publications
1
72
0
2
Order By: Relevance
“…Triple negative breast cancer (TNBC), accounting for about 15% human breast cancer, is known to be highly aggressive and resistant to conventional therapies due to their lack of well-known targets [114]. We found that TNBCs are mostly COX-2 positive [49], also reported by other investigators [115].…”
Section: Cox-2/ep Receptors and Breast Cancersupporting
confidence: 67%
“…Triple negative breast cancer (TNBC), accounting for about 15% human breast cancer, is known to be highly aggressive and resistant to conventional therapies due to their lack of well-known targets [114]. We found that TNBCs are mostly COX-2 positive [49], also reported by other investigators [115].…”
Section: Cox-2/ep Receptors and Breast Cancersupporting
confidence: 67%
“…Triple-negative breast cancer (TNBC), accounting for about 15% of human breast cancers, is known to be highly aggressive and resistant to conventional therapies due to their lack of well-known targets [ 126 ]. We found that TNBCs are mostly COX-2-positive [ 53 ], also reported by other investigators [ 127 ].…”
Section: Cox-2-mediated Molecular Pathways: Key Events In the Syntmentioning
confidence: 99%
“…Immunotherapy for TNBC has accelerated the research on immuno-oncology drugs as shown in Figure 6 [ 92 , 93 ]. The FDA has approved the combination of Tecentriq (atezolizumab) and Abraxane (nab-paclitaxel) for the front-line treatment of patients with metastatic PD-L1-positive TNBC as shown in Figure 3 and Table 4 [ 92 , 93 ].…”
Section: Immunotherapymentioning
confidence: 99%